Validation of the International Study Group of Rectal Cancer definition and severity grading of anastomotic leakage - Kulu, Yakup; Ulrich, Alexis; Bruckner, Thomas; Contin, Pietro; Welsch, Thilo; Rahbari, Nuh Nabi; Büchler, Markus W.; Weitz, Jürgen (Surgery, 2013)
Background - The International Study Group of Rectal Cancer (ISREC) has proposed a generally applicable definition and severity grading of (AL) after sphincter-preserving resection of the rectum. This work has been carried out to test for validity. - Methods - A total of 746 patients who were identified from a prospective rectal cancer database underwent sphincter-preserving anterior resection of the rectum between October 2001 and January 2011. The incidence and severity of AL was determined using the criteria established by the ISREC. Patients with AL were categorized according to the ISREC scheme. The clinical outcomes were analyzed and compared between the groups. - Results - The overall AL rate was 7.5% (56/746). The 56 patients with AL were distributed among the different groups as follows: Grade A, 16%; grade B, 23%; and grade C, 61%. Compared with the grade A patients, grades B and C patients had significantly elevated serum C-reactive protein levels (P < .01). None of the grade A patients were transferred to the intensive care unit (ICU). Their further hospital stay was uneventful. The length of stay in the ICU was significantly longer for grade C patients compared with grade B patients (P < .001). The median hospital stay of grade C patients was significantly longer than that of grades A and B patients (P < .001). - Conclusion - The definition and severity grading of AL after anterior resection of the rectum proposed by the ISREC provides a simple, easily applicable, and valid classification. Using this classification system may facilitate comparison of results from different studies on AL after sphincter-preserving rectal surgery.
Gesehen am 30.06.2021